Enigma of the high prevalence of anti-SARS-CoV-2 antibodies in HIV-positive people with no symptoms of COVID-19 in Burkina Faso - Tani Sagna; Paul Ouedraogo; Lassina Traore; Dorcas Obiri-Yeboah; Albert Yonli; Aristide Tapsoba; Frida Tovo; Abel Sorgho; Laetitia Zongo; Ouego Nikiema; Denise Ilboudo; Marius Belemgnegre; et al. (Journal of Public Health in Africa, 2022)
The severe acute respiratory syndrome due to the new coronavirus (SARS-CoV-2), responsible for coronavirus disease (COVID-19), has severely tested the global health response capacity, with predictions of a fatality for developing countries. To evaluate the prevalence of anti-SARS-CoV- 2 antibodies in People Living with HIV (PLHIV) with no COVID-19 symptoms in Burkina Faso. Seroprevalence was estimated by performing a qualitative screening test for SARS-CoV-2-specific immunoglobulins. The STANDARDTM Q COVID-19 IgM/IgG Combo Test kit from SD BIOSENSOR was used. Parameters like HIV plasma viral load, CD4 T cell count and C-Reactive Protein (CRP) expression were estimated. This study enrolled a total of 200 PLHIV aged 4-87 years who are asymptomatic for COVID-19. There were 36 (18%) positive for SARS-CoV-2 IgM and/or IgG of which three (1.50%) were positive for SARS-CoV-2 IgM and 33 (16.50%) for IgG. Among participants diagnosed as IgM positive, 66.67% (2/3) had the highest HIV viral loads with the lowest CD4 T cell counts (p0.0001). The expression of CRP was relatively higher in COVID-19 IgG positive individuals (7.95±12.5 mg/L) than negative individuals (6.26±6.92 mg/L; p=0.37). The rate of IgG and IgM SARS-CoV-2 immunoglobulin carriage (18%), accompanied by a relatively high CRP levels, was revealed in this study among PLHIV. This serologic evidence and mild inflammation suggest that Burkina Faso escaped the worst, not necessarily because there were not many SARS-CoV-2 infections in its population, but because factors including genetic and environmental, might have resulted in many asymptomatic carriers.